Simulation tool for assessing the release and environmental distribution of nanomaterials - Liu, Haoyang Haven; Bilal, Muhammad; Lazareva, Anastasiya; Keller, Arturo; Cohen, Yoram (Beilstein Journal of Nanotechnology, 2015)
An integrated simulation tool was developed for assessing the potential release and environmental distribution of nanomaterials (RedNano) based on a life cycle assessment approach and multimedia compartmental modeling coupled with mechanistic intermedia transport processes. The RedNano simulation tool and its web-based software implementation enables rapid “what-if?” scenario analysis, in order to assess the response of an environmental system to various release scenarios of engineered nanomaterials (ENMs). It also allows for the investigation of the impact of geographical and meteorological parameters on ENM distribution in the environment, comparison of the impact of ENM production and potential releases on different regions, and estimation of source release rates based on monitored ENM concentrations. Moreover, the RedNano simulation tool is suitable for research, academic, and regulatory purposes. Specifically, it has been used in environmental multimedia impact assessment courses at both the undergraduate and graduate levels. The RedNano simulation tool can also serve as a decision support tool to rapidly and critically assess the potential environmental implications of ENMs and thus ensure that nanotechnology is developed in a productive and environmentally responsible manner.
Keywords: engineered nanomaterials; environmental exposure assessment; life cycle assessment; nanoinformatics; web-based simulation tool

Fundamentals and Applications of Nanomaterials - Guo, Z.; Tan, L. (Artech House Publishers, 2009)

(untitled) - Handy, R. D.; Owen, R.; Valsami-Jones, E. (Ecotoxicology, 2008)

(untitled) - Klaine, S. J.; Alvarez, P. J. J.; Batley, G. E.; Fernandes, T. F.; Handy, R. D.; Lyon, D. Y.; Mahendra, S.; McLaughlin, M. J.; Lead, J. R. (Environ. Toxicol. Chem., 2008)

(untitled) - Wiesner, M. R.; Lowry, G. V.; Alvarez, P.; Dionysiou, D.; Biswas, P. (Environ. Sci. Technol., 2006)

(untitled) - Cohen, Y.; Rallo, R.; Liu, R.; Liu, H. H. (Acc. Chem. Res., 2013)

(untitled) - Keller, A.; McFerran, S.; Lazareva, A.; Suh, S. (J. Nanopart. Res., 2013)

(untitled) - Sun, T. Y.; Gottschalk, F.; Hungerbuhler, K.; Nowack, B. (Environ. Pollut., 2014)

(untitled) - Liu, H. H.; Cohen, Y. (Environ. Sci. Technol., 2014)

(untitled) - Praetorius, A.; Scheringer, M.; Hungerbühler, K. (Environ. Sci. Technol., 2012)

(untitled) - Meesters, J. A. J.; Koelmans, A. A.; Quik, J. T. K.; Hendriks, A. J.; van de Meentt, D. (Environ. Sci. Technol., 2014)

Multimedia environmental models: the fugacity approach - Mackay, D. (CRC Press, 2001)

(untitled) - Cohen, Y.; Cooter, E. J. (Pract. Period. Hazard., Toxic, Radioact. Waste Manage., 2002)

(untitled) - Cohen, Y.; Cooter, E. J. (Pract. Period. Hazard., Toxic, Radioact. Waste Manage., 2002)

CalTOX, a multimedia total exposure model for hazardous-waste sites; Part 1, Executive summary - McKone, T. E. (California Environmental Protection Agency, 1993)

(untitled) - Gottschalk, F.; Sonderer, T.; Scholz, R. W.; Nowack, B. (Environ. Sci. Technol., 2009)

(untitled) - Gottschalk, F.; Scholz, R. W.; Nowack, B. (Environ. Model. Software, 2010)

(untitled) - Gottschalk, F.; Sonderer, T.; Scholz, R. W.; Nowack, B. (Environ. Toxicol. Chem., 2010)

(untitled) - Pirrone, N.; Keeler, G. J.; Holsen, T. M. (Environ. Sci. Technol., 1995)

(untitled) - Simcik, M. F.; Franz, T. P.; Zhang, H.; Eisenreich, S. J. (Environ. Sci. Technol., 1998)

(untitled) - Ryan, P. A.; Cohen, Y. (Chemosphere, 1986)

(untitled) - Yaffe, D.; Cohen, Y.; Arey, J.; Grosovsky, A. J. (Risk Anal., 2001)

(untitled) - Harrison, R. M.; Smith, D. J. T.; Luhana, L. (Environ. Sci. Technol., 1996)

(untitled) - Lazareva, A.; Keller, A. A. (ACS Sustainable Chem. Eng., 2014)

Smoke, dust, and haze: fundamentals of aerosol dynamics - Friedlander, S. K. (Oxford University Press, 2000)

(untitled) - Friedlander, S. K.; Wang, C. S. (J. Colloid Interface Sci., 1966)

Atmospheric chemistry and physics: from air pollution to climate change - Seinfeld, J. H.; Pandis, S. N. (John Wiley & Sons, 2006)

(untitled) - Farley, K. J.; Morel, F. M. M. (Environ. Sci. Technol., 1986)

(untitled) - Spicer, P. T.; Pratsinis, S. E. (AIChE J., 1996)

Solving ordinary differential equations - Hairer, E.; Nørsett, S. P.; Wanner, G. (Springer Verlag, 1987)

(untitled) - Braakhuis, H. M.; Cassee, F. R.; Fokkens, P. H. B.; de la Fonteyne, L. J. J.; Oomen, A. G.; Krystek, P.; de Jong, W. H.; van Loveren, H.; Park, M. V. D. Z. (Nanotoxicology, 2015)

(untitled) - Cohen, J. M.; Teeguarden, J. G.; Demokritou, P. (Part. Fibre Toxicol., 2014)

The World Factbook

National Climatic Data Center: Climate Data Online

Municipal waste treatment - United Nations Statistics Division

Human Development Reports 2012. International Human Development Indicators: Inequality-adjusted HDI value - United Nations Development Programme (UNDP, 2012)

(untitled) - Giorgi, F. (J. Geophys. Res.: Atmos., 1986)

Daily Observational Data: Global Summary of the Day (GSOD)

“Rains” in Glossary of Meteorology - American Meteorological Society

Fact sheet No. 3 - Water in the atmosphere, National Meteorological Library and Archive - Met Office, United Kingdom

Water: Sewage Sludge (Biosolids), Frequently Asked Questions - United States Environmental Protection Agency

(untitled) - Holden, P. A.; Klaessig, F.; Turco, R. F.; Priester, J. H.; Rico, C. M.; Avila-Arias, H.; Mortimer, M.; Pacpaco, K.; Gardea-Torresdey, J. L. (Environ. Sci. Technol., 2014)

(untitled) - Kaegi, R.; Ulrich, A.; Sinnet, B.; Vonbank, R.; Wichser, A.; Zuleeg, S.; Simmler, H.; Brunner, S.; Vonmont, H.; Burkhardt, M.; Boller, M. (Environ. Pollut., 2008)

(untitled) - Keller, A. A.; Vosti, W.; Wang, H.; Lazareva, A. (J. Nanopart. Res., 2014)

(untitled) - Park, B.; Donaldson, K.; Duffin, R.; Tran, L.; Kelly, F.; Mudway, I.; Morin, J.-P.; Guest, R.; Jenkinson, P.; Samaras, Z.; Giannouli, M.; Kouridis, H.; et al. (Inhalation Toxicol., 2008)